A Positive Perspective Study of Online Game: Children's English Acquisition from Online Game Habit - Djafar, Hariyanti; HJ Wahid, Jusmin; Umasugi, Faujia; Nasir, Vebiyanti; Sahmadan, Safrudin (INTERACTION: Jurnal Pendidikan Bahasa, 2024)
The phenomenon of online gaming is certainly a concern for all parents. Not only in Indonesia but also around the world. Ternate North Maluku is one of the cities in Indonesia that became the site of this current study, which explains the phenomenon of online games taking place and their role in children's autonomous English learning. This study is located in Jerbus Village, South Ternate. To provide more honest and accurate data, the interviews were semi-structured with 11 children aged 7 to 12 years old. Employing a descriptive qualitative design, the data analysis and interpretation used raw data, preparing data for analysis, collecting the data on the computer, coding data, relating themes, and interpreting the meaning of themes and descriptions (Creswell, 2009, p. 185). The results of this study explain that online games encourage children to learn English independently without any coercion from others. It also helps them learn English naturally and contributes to children's English acquisition. This research conclusion is that online games have so far only been considered to bring negative influences to children who have been addicted, such as the absence of socialization, lack of social interaction, affecting the quality of learning, and many other negative influences. This current study proves that online games also have a positive side. The positive role is to replace lost face-to-face social interaction with online interaction. In addition, the online game stimulated children's communication using English